Evaluating and Enhancing Driving Skills for Individuals With Intellectual Disabilities Through Simulator Training. (December 2021) - Randall, Kristina N.; Ryan, Joseph B.; Stierle, Jordan N.; Walters, Sharon M.; Bridges, William
Research consistently demonstrates that attainment of a driver's license and access to a vehicle directly and favorably influence employment outcomes, enhance one's ability to capitalize on quality jobs, and expand one's access to community and independent opportunities. This study used a driving simulator to provide driving lessons to 12 young adults with intellectual disabilities (IDs). The purpose was to use a safe learning environment to screen candidates for those who showed the potential to obtain a driver's license. Instruction was provided using a set of interactive exercises focusing on controlling the vehicle via lane keeping, speed maintenance, and obstacle avoidance tasks. Results revealed that simulator training provided a safe learning environment to identify individuals demonstrating the potential to safely operate a motor vehicle. Participants demonstrated moderate to large gains in maintaining lane position, speed, braking response, and target detection. Implications and suggestions for future research are provided.